Isolated intramedullary tuberculoma as the initial presentation of disseminated tuberculosis: A case report - Begam, Rezwana Naher; Sharma, Ishan; Ali, Liyaqat; Parvez, Anjum; Amir , Syed Hasan (Indian Journal of Case Reports, 2026)
Spinal intramedullary tuberculoma is a rare manifestation of central nervous system tuberculosis (TB) and an uncommon cause of acute transverse myelitis. We report a 38-year-old man who presented with fever, low back pain, rapidly progressive paraplegia, sensory impairment, and urinary retention. Magnetic resonance imaging of the spine revealed intramedullary T2 hyperintensity extending from T11 to L1 with thick ring enhancement at T11, consistent with an intramedullary tuberculoma associated with tuberculous myelitis. HIV testing was negative. Additional imaging demonstrated pulmonary involvement with pleural effusion and multiple intracranial tuberculomas, suggestive of disseminated TB. The patient showed partial neurological improvement following initiation of corticosteroids and antitubercular therapy. This case highlights the importance of maintaining a high index of suspicion for TB in patients presenting with acute myelopathy in endemic regions, even in the absence of microbiological confirmation, as early diagnosis is crucial to prevent permanent neurological deficits.